2021
DOI: 10.1242/jcs.249763
|View full text |Cite
|
Sign up to set email alerts
|

Suv420 enrichment at the centromere limits Aurora B localization and function

Abstract: Centromere structure and function are defined by the epigenetic modification of histones at centromeric and pericentromeric chromatin. The constitutive heterochromatin found at pericentromeric regions is highly enriched for H3K9me3 and H4K20me3. While mis-expression of the methyltransferase enzymes, Suv39 and Suv420, that regulate these marks are common in disease, the consequences of such changes are not well understood. Our data show that increased centromere localization of Suv39 and Suv420 suppress centrom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“… 29 A recent study showed that loss of H4K20me3 reduced Aurora B activity at centromeres. 30 Although this remains to be tested, it is possible that TopoIIα regulates Aurora B recruitment by binding to centromeric nucleosomes containing H4K20me3. It will also be important to test if H3K27me3 contributes to centromeric Aurora B activity.…”
Section: Discussionmentioning
confidence: 99%
“… 29 A recent study showed that loss of H4K20me3 reduced Aurora B activity at centromeres. 30 Although this remains to be tested, it is possible that TopoIIα regulates Aurora B recruitment by binding to centromeric nucleosomes containing H4K20me3. It will also be important to test if H3K27me3 contributes to centromeric Aurora B activity.…”
Section: Discussionmentioning
confidence: 99%
“…RB interacts with SUV420H, and the defects in histone methylation, cohesin binding, and CIN are reversed by overexpression of SUV420H in RB-deficient cells ( 11 , 13 ). Importantly, a recent study showed that AURKB is recruited to kinetochores when SUV420H is inhibited and, at kinetochores, helps prevent chromosome misalignments and missegregations ( 14 ). Lastly, RB loss increases activity of the transcription factor E2F1, which promotes AURKB gene expression ( 15 ).…”
Section: Rb Loss Can Render Sclcs Sensitive To Aurkb Inhibitorsmentioning
confidence: 99%
“…Nonetheless, the roles of KMT5C and H4K20me3 in tumorigenesis are clearly context dependent. Expression data from The Cancer Genome Atlas (TCGA) indicates that KMT5C is highly expressed in cancers ( Herlihy et al, 2021 ). And, increased expression of H4K20me3 was reported in esophageal squamous cell carcinoma tumor tissues ( Zhou et al, 2019 ) and in pancreatic cancer, where KMT5C is reported to favor mesenchymal identity, while KMT5C knockdown decreased stemness and increased drug sensitivity ( Viotti et al, 2018 ).…”
Section: Role Of H4k20me3 In Heterochromatin Formation and Structurementioning
confidence: 99%